Numerical studies of thermal flying height control slider in hard disk drive - Chan, Ze Wei. (2010)
As thermal flying height control (TFC) slider has been widely used in today's hard disk drive (HDD) industry for its advantages of easier control of flying height (FH) and less risk of contacts with the disk over conventional slider. The concept of a TFC slider is to use a heater embedded near the read/write element. When a current is applied through the heater, the pole-tip protrusion caused by the mismatch of thermal expansion of various materials occurs and reduces the slider-disk spacing accordingly. Test, analysis and design of the air bearing slider with thermal protrusion are essential for both research and development work, and industrial products.